The Influence of Landscape Composition on The Diversity and Abundance of Beetles in Rice Cultivation - Ruwaidah, Nisa; Rizali, Akhmad (Journal of Tropical Plant Protection, 2022)
The objectives of this study were to examine the characteristics of the landscape at each research site to examine the diversity, abundance, and composition of beetles; to examine the effect of management practices and habitat conditions, and to examine the relationship between landscape composition and beetle diversity and abundance at 14 research sites. The research was conducted from January 2022 to March 2022 in 14 rice farming locations spread across West Sumatra, Central Java, and East Java. Sampling was done by installing light traps at each location, mapping the landscape condition, and characterizing the landscape by conducting a ground survey at a radius of 500 m from the observation plot by recording various types of land use and then digitizing it with the QGIS application version 3.24.1. This study used analysis of variance and regression analysis. The results showed that plantations, agriculture, forests, and settlements dominated the land use types. The total number of beetles was 12,653, consisting of 10 families and 24 morphospecies. The cultivation method that influences the diversity of beetles is the application of fertilizer, while the landscape composition that affects species diversity is natural habitat and class area plantation.